2011
DOI: 10.3109/00365521.2011.619276
|View full text |Cite
|
Sign up to set email alerts
|

Disaccharidase deficiency in pediatric patients with celiac disease and intact villi

Abstract: There is a profound deficiency of DS levels in pediatric patients with CD who have intact villi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
1
15
0
1
Order By: Relevance
“…Measurement of DS activities provides additional information at the time of diagnosis and during follow-up to assess the response to a GFD [19]. Furthermore, it has been shown that determining DS activities might aid the diagnosis of CD where milder histological changes are seen, including Marsh I and II [20] abnormalities in small intestinal biopsies [4, 10, 18]. …”
Section: Diagnostic Aspects Of Small Intestinal Disaccharidase Actmentioning
confidence: 99%
See 2 more Smart Citations
“…Measurement of DS activities provides additional information at the time of diagnosis and during follow-up to assess the response to a GFD [19]. Furthermore, it has been shown that determining DS activities might aid the diagnosis of CD where milder histological changes are seen, including Marsh I and II [20] abnormalities in small intestinal biopsies [4, 10, 18]. …”
Section: Diagnostic Aspects Of Small Intestinal Disaccharidase Actmentioning
confidence: 99%
“…Milder biopsy changes that are limited to lymphocytic infiltration with or without crypt hyperplasia may require additional data in order to increase the certainty of a diagnosis of CD, as these histological changes are not exclusive to CD [4]. The diagnosis of CD may be enhanced by genotyping (HLA-DQ2 or HLA-DQ8); serological markers [4] and immunohistochemical staining of the γδ +ve intraepithelial lymphocytes found in patients with CD may also be used to confirm the diagnosis [24, 25].…”
Section: Diagnostic Aspects Of Small Intestinal Disaccharidase Actmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with untreated celiac disease occur malnutrition, the mild forms may show malabsorption of iron, sideropenia and sideropenic anemia, not shown in nonCaucasians [39], metabolic bone disease due to malabsorption of calcium and vitamin D. [40] Parts is also lactose intolerance and deficiencies of other disaccharidases, even in patients with Marsh I histology [41], hypovitaminosis of vitamin B complex and vitamin C. Therefore, these symptoms should us lead to exclusion of celiac disease [40]. Severe forms of celiac disease with the destruction of the intestinal mucosa lead to severe proteinoenergetic malnutrition.…”
Section: Gluten Free Diet and Its Consequences Celiac Disease And Glmentioning
confidence: 99%
“…[59][60][61][62] Moreover, regulatory mechanisms pinpointing MLCK activation in various subcellular regions, i.e. TW and PAMR, for differential control of transcellular and paracellular barriers remain poorly understood.…”
Section: Terminal Web Contraction and Brush Border Fanningmentioning
confidence: 99%